Dormitory-Based Experiential English Immersion and Proficiency Outcomes Among Maritime Cadets - Muh. Hasrun Fitriady; Nur Aeni; Andi Asrifan (Journal La Edusci, 2026)
This study evaluated whether the DREAM (Dormitory for Real English Acquisition and Mastery) Dormitory, an experiential English immersion program at the Merchant Marine Polytechnic of Makassar (PIP Makassar), improved maritime cadets’ English proficiency. Grounded in experiential learning theory, the program requires cadets to use English in structured and informal daily activities. A quantitative one-group pre-test–post-test pre-experimental design was applied. Participants were first-year male cadets residing in Dormitory C2, and a TOEIC prediction test measuring listening, reading, speaking, and writing was administered before and after participation in the program. A total of 179 cadets were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-sample t-test, with Cohen’s d computed as the effect size. The results showed that the mean total TOEIC score increased significantly from 646.37 (SD = 223.12) to 816.90 (SD = 228.42), a mean gain of 170.53 points, t(178) = 11.13, p < .001, with a large effect size (d = 0.83). All four skills improved significantly, with reading, writing, and listening showing moderate effects and speaking the smallest gain. Improvement was observed in 80.4% of cadets, and intermediate-level cadets gained the most. The findings indicate that experiential, dormitory-based English immersion was associated with meaningful proficiency gains in a maritime education setting, supporting continued institutional investment in structured immersion environments.